Factors Associated With the Use of Postoperative Analgesics in Patients Undergoing Direct Microlaryngoscopy. (May 2017) - Taliercio, Salvatore; Sanders, Brian; Achlatis, Stratos; Fang, Yixin; Branski, Ryan; Amin, Milan
Objective: Morbidity associated with suspension laryngoscopy has been well documented. However, standard of care with regard to postoperative analgesia has not been described, and anecdotal evidence suggests wide variability with regard to postoperative narcotic and non-narcotic recommendations. We sought to quantify the postoperative course following suspension microlaryngoscopy by relating patient-based and intraoperative measures with analgesic use. Methods: Body mass index (BMI), Friedman tongue position (FTP), and Mallampati scores as well as laryngoscope type, number of attempts required for optimal visualization, and suspension time were documented in 50 consecutive patients undergoing routine suspension microlaryngoscopy. Postoperative symptoms and analgesic use was queried on postoperative days 1, 3, and 10. Results: In this cohort, 62.5% employed postoperative analgesia. However, only 20% required narcotics. No difference in suspension time was identified in those taking analgesics (33.0 vs 37.3 minutes, P = .44). In addition, no relationship between procedure type and the need for analgesia was noted. The majority of patients (76%) described sore throat persisting for 3 postoperative days; 36% reported sore throat persisting beyond postoperative day 3. Conclusions: The majority of patients undergoing microlaryngoscopy reported discomfort, but symptoms were largely ameliorated with over-the-counter analgesics. Routine prescription of narcotics following routine suspension laryngoscopy may be unnecessary.